The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1101/2020.12.16.423115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methane-derived carbon flow through host-virus trophic networks in soil

Abstract: The concentration of atmospheric methane continues to increase with microbial communities controlling soil-atmosphere fluxes. While there is substantial knowledge of the diversity and function of organisms regulating methane production and consumption, the frequency and impact of interactions with viruses on their activity in soil is unknown. Metagenomic sequencing of soil microbial communities has enabled identification of linkages between viruses and hosts. However, determining host-virus linkages through se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Capsid, terminase, portal and integrase protein sequences from these proviruses were subsequently used as search queries. While previous analysis of 12 total soil metagenome or virome libraries from the same soil samples did not enable identification of any AOA-associated virus contigs (average of 152 million quality filtered reads and 1,947 contigs ³10 kb per library) [14], this targeted approach using LBD DNA from nitrifying microcosms yielded 64 contigs predicted as derived from AOA-infecting viruses and each representing a unique vOTU. In addition, viruses infecting other nitrifier populations were identified with five and three vOTUs derived from viruses infecting ammonia-oxidising bacteria (AOB) and NOB, respectively.…”
Section: Aoa Virusesmentioning
confidence: 82%
See 3 more Smart Citations
“…Capsid, terminase, portal and integrase protein sequences from these proviruses were subsequently used as search queries. While previous analysis of 12 total soil metagenome or virome libraries from the same soil samples did not enable identification of any AOA-associated virus contigs (average of 152 million quality filtered reads and 1,947 contigs ³10 kb per library) [14], this targeted approach using LBD DNA from nitrifying microcosms yielded 64 contigs predicted as derived from AOA-infecting viruses and each representing a unique vOTU. In addition, viruses infecting other nitrifier populations were identified with five and three vOTUs derived from viruses infecting ammonia-oxidising bacteria (AOB) and NOB, respectively.…”
Section: Aoa Virusesmentioning
confidence: 82%
“…A homologue-based approach was also used where an AOA host was predicted when 'best hit' shared homologues with those in genomes of Thaumarchaeota (NCBI taxonomy) were ≥3x more abundant compared to the second most dominant phylum [26]. Unlike our previous DNA-SIP analysis of methanotroph populations and associated viruses in these soils [27], spacer sequences in AOA MAG CRISPR arrays only matched predicted AOA viruses from other studies with 2 mismatches between spacer and protospacer sequences and none from this study (data not shown).…”
Section: Identification Of Putative Viruses Infecting Nitrifiersmentioning
confidence: 99%
See 2 more Smart Citations
“…Some phenomena have been suggested to modulate methane oxidation rates. For example, some phages can decrease methane oxidation rates by infection and lysis of methane-oxidizing bacteria 8 and others with the critical subunit of MMO 9 likely increase the ability of their host bacteria to generate energy during phage replication. Here, we report the discovery of novel extrachromosomal elements that clearly replicate within Methanoperedens.…”
Section: Introductionmentioning
confidence: 99%